2012
DOI: 10.1177/0886109912464477
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Attitudes Toward Aging Among Older Women in Turkey

Abstract: This quantitative and descriptive study investigated the quality of life (QOL) and attitudes toward aging of 270 older women in Sanliurfa Province, Turkey. The Turkish versions of the World Health Organization Quality of Life Instrument-Older Adults Module and the World Health Organization-Attitudes Toward Aging Questionnaire were administered to the participants. The results indicated that there was significant relationship between the women's QOL and attitudes toward aging. Two dimensions of attitudes toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…Consistent with other studies (Kalfoss et al 26 and Top et al 15 , 16 ), significant correlations are reported between most AAQ dimensions and WHOQOL facets. All these findings demonstrate associations between attitudes toward one’s own aging and QoL in different cultures such as Norwegian, English Canadian, Spanish, Belgian and Turkish populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with other studies (Kalfoss et al 26 and Top et al 15 , 16 ), significant correlations are reported between most AAQ dimensions and WHOQOL facets. All these findings demonstrate associations between attitudes toward one’s own aging and QoL in different cultures such as Norwegian, English Canadian, Spanish, Belgian and Turkish populations.…”
Section: Discussionsupporting
confidence: 90%
“…All these findings demonstrate associations between attitudes toward one’s own aging and QoL in different cultures such as Norwegian, English Canadian, Spanish, Belgian and Turkish populations. 15 , 16 , 26 , 28 Furthermore, a global study indicates that attitudes toward one’s own aging assessed using the AAQ might mediate the relationship between QoL and satisfaction with health. 43 This cross-sectional study of 4,593 older adults from different countries demonstrated that those people who were dissatisfied with their health had more negative attitudes toward their own aging process, which led them to experience a poorer QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the poor-quality-of-life domain, all of the 29 studies and 93.9% of the 45 associations found evidence of ageism. For example, negative self-perceptions of aging predicted worse quality-of-life among socio-economically disadvantaged older Turkish women [66].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…Attitudes toward one’s own aging include affective, cognitive and evaluative components of behavior regarding the process of aging as a personal experience ( Hess, 2006 ). Recent cross-sectional studies have demonstrated that negative attitudes toward one’s own aging, measured by the Attitudes to Aging Questionnaire, ( AAQ; Laidlaw, Power, & Schmidt, 2007 ), are strongly associated with lower quality of life ( Top & Dikmetas, 2012 ; Top, Eris, & Kabalcioglu, 2012a , 2012b ). In addition, several longitudinal studies have shown that attitudes toward one’s own aging, usually assessed by the Attitude toward own aging subscale (ATOA) of the Philadelphia Geriatric Moral Scale ( PGCMS; Lawton, 1975 ) can have either deleterious or beneficial long-term effects on various health outcomes, depending on their negative or positive valence.…”
Section: Introductionmentioning
confidence: 99%